Historical Study of the Origins of the Kalam Issue in the Rise of Islam - Nur’Afni Maulina Maghfiro; Maulidatul Aulia; Khainuddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article discusses the origins of the Kalam issue in the context of the Islamic revival, with a focus on historical review. Kalam, which refers to rational theology in Islam, has been the focus of extensive debate and research in the history of Islamic thought. By delving into its historical roots, this article explores the early development of Kalam from the early days of Islam to its golden age during the period of Islamic intellectual revival. Through this historical approach, this article aims to provide a better understanding of how and why the Kalam issue became so important in Islamic thought, as well as its impact on the development of the Islamic intellectual tradition as a whole.